If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6=-3(r+16)
We move all terms to the left:
-6-(-3(r+16))=0
We calculate terms in parentheses: -(-3(r+16)), so:We get rid of parentheses
-3(r+16)
We multiply parentheses
-3r-48
Back to the equation:
-(-3r-48)
3r+48-6=0
We add all the numbers together, and all the variables
3r+42=0
We move all terms containing r to the left, all other terms to the right
3r=-42
r=-42/3
r=-14
| 2(0,5x+2)=39x-72 | | |3x-14|=4x | | 6=9m+12m | | -9m+12m=6 | | 9x-1=6-15x | | 2x^2-(3x-1)=0 | | -3(h+4)=6 | | 4-3x=5-6x7 | | 11=3(z-8)-7 | | 4(2x+3)=6x+6 | | 5=+6(3h+4) | | 88-s=8 | | -7=3(r-10)-7 | | 10^5n=4199999999958 | | x=16x-3/2=20 | | 5x-28=x-32 | | -3.1x+7-7.4x=-6(x-2/3) | | 8x^2-16x-64=0 | | 6(6n+5)=5(8n+10) | | (t+8)(-2)=1.8 | | a÷6+6=11 | | 1/8x+5=6 | | 10x-1-3x-5=8 | | 1/3+c=5/3 | | X-20/x+280=x | | 2x+4-(-3x+2)=0 | | 45+8s=88 | | 2x+24=6x+89099767865736 | | 6x-22=-58 | | x+5=5/2x-4=3 | | −2x+8=−0 | | (3n+3)/3=9 |